Conductivity Tuning via Doping with Electron Donating and Withdrawing Molecules in Perovskite CsPbI3 Nanocrystal Films. Issue 27 (10th May 2019) - Gaulding, E. Ashley; Hao, Ji; Kang, Hyun Suk; Miller, Elisa M.; Habisreutinger, Severin N.; Zhao, Qian; Hazarika, Abhijit; Sercel, Peter C.; Luther, Joseph M.; Blackburn, Jeffrey L.
Abstract: Doping of semiconductors enables fine control over the excess charge carriers, and thus the overall electronic properties, crucial to many technologies. Controlled doping in lead‐halide perovskite semiconductors has thus far proven to be difficult. However, lower dimensional perovskites such as nanocrystals, with their high surface‐area‐to‐volume ratio, are particularly well‐suited for doping via ground‐state molecular charge transfer. Here, the tunability of the electronic properties of perovskite nanocrystal arrays is detailed using physically adsorbed molecular dopants. Incorporation of the dopant molecules into electronically coupled CsPbI3 nanocrystal arrays is confirmed via infrared and photoelectron spectroscopies. Untreated CsPbI3 nanocrystal films are found to be slightly p‐type with increasing conductivity achieved by incorporating the electron‐accepting dopant 2, 3, 5, 6‐tetrafluoro‐7, 7, 8, 8‐tetracyanoquinodimethane (F4 TCNQ) and decreasing conductivity for the electron‐donating dopant benzyl viologen. Time‐resolved spectroscopic measurements reveal the time scales of Auger‐mediated recombination in the presence of excess electrons or holes. Microwave conductance and field‐effect transistor measurements demonstrate that both the local and long‐range hole mobility are improved by F4 TCNQ doping of the nanocrystal arrays. The improved hole mobility in photoexcited p‐type arrays leads to a pronounced enhancement in phototransistors. Abstract : Molecular doping is demonstrated as a powerful strategy for enhancing electrical conductivity in arrays of electronically coupled CsPbI3 nanocrystals. The high surface‐area‐to‐volume ratio enables physisorbed organic redox molecules to inject charge carriers into a nanocrystal array. p‐Type doping improves both ground‐state conductivity and photoconductivity, enabling pronounced performance enhancements to both transistors and phototransistors.